Management of stable chronic pulmonary obstructive disease - Jáuregui Antúnez, Javier (2009)
Chronic obstructive pulmonary disease (COPD) is a preventable and treatable condition. Its lung component is characterized by an airflow obstruction that is not completely reversible. Available evidence shows that some components of respiratory rehabilitation programs bring benefits for patients with symptomatic COPD; however, it is not quite clear whether this benefit translates into less expenditure in healthcare.